Human proximal tubular epithelial cell interleukin-1 receptor signalling triggers G2/M arrest and cellular senescence during hypoxic kidney injury - Kurt T. K. Giuliani; Purba Nag; Benjamin C. Adams; Xiangju Wang; Seokchan Hong; Anca Grivei; Rebecca L. Johnston; Nicola Waddell; Kenneth K. C. Ho; Yilin Tian; Muhammad Ali Khan; Chang Seong Kim; et al. (Cell Death and Disease)
Abstract Hypoxia and interleukin (IL)-1β are independent mediators of tubulointerstitial fibrosis, the histological hallmark of chronic kidney disease (CKD). Here, we examine how hypoxia and IL-1β act in synergy to augment maladaptive proximal tubular epithelial cell (PTEC) repair in human CKD. Ex vivo patient-derived PTECs were cultured under normoxic (21% O2) or hypoxic (1% O2) conditions in the absence or presence of IL-1β and examined for maladaptive repair signatures. Hypoxic PTECs incubated with IL-1β displayed a discrete transcriptomic profile distinct from PTECs cultured under hypoxia alone, IL-1β alone or under normoxia. Hypoxia+IL-1β-treated PTECs had 692 ‘unique’ differentially expressed genes (DEGs) compared to normoxic PTECs, with ‘cell cycle’ the most significantly enriched KEGG pathway based on ‘unique’ down-regulated DEGs (including CCNA2, CCNB1 and CCNB2). Hypoxia+IL-1β-treated PTECs displayed signatures of cellular senescence, with reduced proliferation, G2/M cell cycle arrest, increased p21 expression, elevated senescence-associated β-galactosidase (SA-β-gal) activity and increased production of pro-inflammatory/fibrotic senescence-associated secretory phenotype (SASP) factors compared to normoxic conditions. Treatment of Hypoxia+IL-1β-treated PTECs with either a type I IL-1 receptor (IL-1RI) neutralizing antibody or a senolytic drug combination, quercetin+dasatinib, attenuated senescent cell burden. In vitro findings were validated in human CKD bio-specimens (kidney tissue, urine), with elevated PTEC IL-1RI expression and senescence (SA-β-gal activity) detected in fibrotic kidneys and numbers of senescent (SA-β-gal+) urinary PTECs correlating with urinary IL-1β levels and severity of interstitial fibrosis. Our data identify a mechanism whereby hypoxia in combination with IL-1β/IL-1RI signalling trigger PTEC senescence, providing novel therapeutic and diagnostic check-points for restoring tubular regeneration in human CKD.